Examining Drivers of Divergence in Recorded and Perceived Human-Carnivore Conflict Hotspots by Integrating Participatory and Ecological Data - Wilkinson, Christine E.; Brashares, Justin S.; Bett, Alice C.; Kelly, Maggi (Frontiers in Conservation Science, 2021)
Human-carnivore conflict is a global challenge with complex and context-specific causes and consequences. While spatial analyses can use ecological principles to predict patterns of conflict, solutions to mitigate conflict must also be locally adaptable, sustainable, and culturally-sensitive. In Nakuru County, Kenya, rapid development and land subdivision have exacerbated conflict by isolating wildlife in protected areas that are increasingly adjacent to human settlements. In an effort to understand local perspectives on carnivore conflict, and to apply this information towards locally-based conservations actions, we conducted gender-stratified interviews and participatory mapping sessions with 378 people in 16 villages near two ecologically isolated protected areas in Kenya: Lake Nakuru National Park and Soysambu Conservancy. Specifically, we developed a method for associating interview responses and demographic information with spatial participatory data to examine how local perceptions of conflict compared to spatially-explicit records of livestock depredation in the region from 2010-2018. We mapped kernel densities of recorded and perceived risk of human-carnivore conflict and then tested for potential social and ecological predictors of divergences found between the two datasets. Mismatched hotspots of observed and perceived risk of conflict were correlated with several ecological and socioeconomic factors. Regions with higher NDVI exhibited more perceived conflict, while the opposite held true for verified conflict. Road density was positively correlated with both types of conflict, and both types of conflict increased closer to protected areas. Livestock ownership, visitation to Lake Nakuru National Park, if the participant’s child walked to school, and male gender identity were associated with more perceived conflict reports. Education level and national park visitation were associated with more positive attitudes toward carnivores. Our results show that while observed and perceived conflict may ultimately be equally important for understanding and managing human-carnivore conflict, they may be driven by markedly different social and ecological processes. We suggest that integrating the spatially explicit experiences and perspectives of local communities with more traditional ecological methods is critical to identifying lasting and socially just forms of conflict mitigation.